Enhanced targeting of invasive glioblastoma cells by peptide-functionalized gold nanorods in hydrogel-based 3D cultures. (August 2017) - Gonçalves, Diana P.N.; Rodriguez, Raul D.; Kurth, Thomas; Bray, Laura J.; Binner, Marcus; Jungnickel, Christiane; Gür, Fatih N.; Poser, Steve W.; Schmidt, Thorsten L.; Zahn, Dietrich R.T.; Androutsellis-Theotokis, Andreas; Schlierf, Michael; et al.
Graphical abstract: Abstract: Cancer stem cells (CSCs) are responsible for drug resistance, tumor recurrence, and metastasis in several cancer types, making their eradication a primary objective in cancer therapy. Glioblastoma Multiforme (GBM) tumors are usually composed of a highly infiltrating CSC subpopulation, which has Nestin as a putative marker. Since the majority of these infiltrating cells are able to elude conventional therapies, we have developed gold nanorods (AuNRs) functionalized with an engineered peptide capable of specific recognition and selective eradication of Nestin positive infiltrating GBM-CSCs. These AuNRs generate heat when irradiated by a near-infrared laser, and cause localized cell damage. Nanoparticle internalization assays performed with GBM-CSCs or Nestin negative cells cultured as two-dimensional (2D) monolayers or embedded in three-dimensional (3D) biodegradable-hydrogels of tunable mechanical properties, revealed that the AuNRs were mainly internalized by GBM-CSCs, and not by Nestin negative cells. The AuNRs were taken up via energy-dependent and caveolae-mediated endocytic mechanisms, and were localized inside endosomes. Photothermal treatments resulted in the selective elimination of GBM-CSCs through cell apoptosis, while Nestin negative cells remained viable. Results also indicated that GBM-CSCs embedded in hydrogels were more resistant to AuNR photothermal treatments than when cultured as 2D monolayers. In summary, the combination of our engineered AuNRs with our tunable hydrogel system has shown the potential to provide an in vitro platform for the evaluation and screening of AuNR-based cancer therapeutics, leading to a substantial advancement in the application of AuNRs for targeted GBM-CSC therapy. Statement of Significance: There is an urgent need for reliable and efficient therapies for the treatment of Glioblastoma Multiforme (GBM), which is currently an untreatable brain tumor form with a very poor patient survival rate. GBM tumors are mostly comprised of cancer stem cells (CSCs), which are responsible for tumor reoccurrence and therapy resistance. We have developed gold nanorods functionalized with an engineered peptide capable of selective recognition and eradication of GBM-CSCs via heat generation by nanorods upon NIR irradiation. An in vitro evaluation of nanorod therapeutic activities was performed in 3D synthetic-biodegradable hydrogel models with distinct biomechanical cues, and compared to 2D cultures. Results indicated that cells cultured in 3D were more resistant to photothermolysis than in 2D systems.